2021
DOI: 10.3390/microorganisms9010107
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Lactobacillus delbrueckii (pExu:hsp65) Prevents the Inflammation and the Disorganization of the Intestinal Mucosa in a Mouse Model of Mucositis

Abstract: 5-Fluorouracil (5-FU) is an antineoplastic drug that causes, as a side effect, intestinal mucositis, acute inflammation in the small bowel. The Heat Shock Protein (Hsp) are highly expressed in inflammatory conditions, developing an important role in immune modulation. Thus, they are potential candidates for the treatment of inflammatory diseases. In the mucositis mouse model, the present study aimed to evaluate the beneficial effect of oral administration of milk fermented by Lactobacillus delbrueckii CIDCA 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 132 publications
(153 reference statements)
3
30
2
Order By: Relevance
“…Neutrophil and eosinophil recruitment in the intestinal mucosa was performed by myeloperoxidase (MPO) and eosinophil peroxidase (EPO) enzyme activities, respectively ( Barroso et al, 2021 ). For this purpose, mice ileum sections were homogenized, centrifuged, and lysed by hypotonic solution with three cycles of freezing and thawing in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil and eosinophil recruitment in the intestinal mucosa was performed by myeloperoxidase (MPO) and eosinophil peroxidase (EPO) enzyme activities, respectively ( Barroso et al, 2021 ). For this purpose, mice ileum sections were homogenized, centrifuged, and lysed by hypotonic solution with three cycles of freezing and thawing in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotic strains, such as Lactobacillus spp., mainly belong to the Lactic Acid Bacteria group (LAB), and they have been investigated as an alternative therapeutic approach against intestinal mucositis ( Batista et al, 2020 ). Several studies have shown the efficacy of various LABs in preventing intestinal mucositis by regulating the microbiota in dysbiosis ( Chang et al, 2018 ), improving the inflammatory process, modulating oxidative stress ( Justino et al, 2015 ; Hu et al, 2020 ; Quaresma et al, 2020 ), and protecting the epithelial barrier by maintaining the integrity of tight junction proteins and goblet cells ( Yeung et al, 2015 ; Barroso et al, 2021 ). Despite these beneficial effects, the use of these inactivated microorganisms has also been highlighted ( Jin et al, 2020 ; Nakai et al, 2021 ; Trindade et al, 2021 ), to minimize possible risks of bacteria translocation producing systemic infections, especially in premature infants or immune-compromised patients ( Doron and Snydman, 2015 ; Zawistowska-Rojek and Tyski, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro reports confirm that different Lactobacillus species downregulate the expression of pro-apoptotic cytokines, i.e., TNFα- and several other pyroptotic or pro-inflammatory cytokines such as IL-1α, IL-1β, IL-2, IL-6, IL-8, IL-17, [ 56 , 58 , 89 , 90 , 139 , 142 ]; whereas other studies showed that the anti-inflammatory cytokine IL-10 is upregulated [ 143 , 144 ]. The pili-like structure from LGG reduces IL-6 expression while increasing the IL-10 production [ 54 ].…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…In vitro assays show that lactobacilli improve the epithelial barrier function against pathogen invasion, contributing to protection of the GI tract from invasive pathogens [ 160 ]. Lactobacilli induce epithelial secretion of mucins MUC2 and MUC3, which improve barrier integrity by preventing microbial adhesion [ 143 , 161 , 162 ]. Zhou et al suggested that the modulation of the mucosal homeostasis and MUC2 expression may be related to lactobacilli EPS [ 163 ].…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…Although clinical trials have shown effectiveness, unfavorable cytotoxic side effects are a huge hurdle that impedes the clinical application of otherwise beneficial cisplatin-based treatments [2][3][4]. Intestinal mucositis, a serious chemotherapy-induced side effect, is characterized by local accumulation of inflammatory cells [5], cell loss in the epithelial barrier [6], increased oxidative stress [7], and reduced gastrointestinal digestive enzyme activities [8]. Clinical manifestations include nausea, vomiting, ulceration, bloating, anorexia, constipation, severe diarrhea, and subsequent weight loss [9][10][11], causing potentially life-threatening complications.…”
Section: Introductionmentioning
confidence: 99%